2022
DOI: 10.1038/s41388-022-02511-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrin regulation by tissue factor promotes cancer stemness and metastatic dissemination in breast cancer

Abstract: Tissue Factor (TF) is the initiator of blood coagulation but also functions as a signal transduction receptor. TF expression in breast cancer is associated with higher tumor grade, metastasis and poor survival. The role of TF signaling on the early phases of metastasis has never been addressed. Here, we show an association between TF expression and metastasis as well as cancer stemness in 574 breast cancer patients. In preclinical models, blockade of TF signaling inhibited metastasis tenfold independent of pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…More recently, it was observed that the transmembrane glycoprotein CD44, a cancer stem cell (CSC) marker, which is also associated with EMT, regulates the expression of TF in breast cancer cells, resulting in enhanced tumor cell procoagulant activity and metastatic dissemination [ 19 ]. TF can also induce EMT, corroborating the evidence that there is a linkage between them [ 20 ]. Blocking of the TF signaling with a monoclonal anti-human TF antibody reduced EMT and CSC programs in breast cancer cells, affecting cell invasion and spheroid formation [ 20 ].…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…More recently, it was observed that the transmembrane glycoprotein CD44, a cancer stem cell (CSC) marker, which is also associated with EMT, regulates the expression of TF in breast cancer cells, resulting in enhanced tumor cell procoagulant activity and metastatic dissemination [ 19 ]. TF can also induce EMT, corroborating the evidence that there is a linkage between them [ 20 ]. Blocking of the TF signaling with a monoclonal anti-human TF antibody reduced EMT and CSC programs in breast cancer cells, affecting cell invasion and spheroid formation [ 20 ].…”
Section: Introductionsupporting
confidence: 77%
“…TF can also induce EMT, corroborating the evidence that there is a linkage between them [ 20 ]. Blocking of the TF signaling with a monoclonal anti-human TF antibody reduced EMT and CSC programs in breast cancer cells, affecting cell invasion and spheroid formation [ 20 ].…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Thus, TF affects early onset of metastasis by affecting cancer stemness via regulation of the expression and function of β 1 and β 4 integrins. For details, see [ 17 ]. FAK, focal adhesion kinase; mAb, monoclonal antibody.…”
Section: Integrin Regulation By Tissue Factor Promotes Cancer Stemnes...mentioning
confidence: 99%